Teaching about sexual minorities and "princess boys": a queer and trans-infused approach to investigating LGBTQ-themed texts in the elementary school classroom. Issue 6 (1st November 2016) - Martino, Wayne; Cumming-Potvin, Wendy
ABSTRACT: This paper is based on research that is concerned to provide insight into the pedagogical potential for interrupting heteronormativity and addressing the politics of gender expression/embodiment in the elementary school classroom. It is informed by an engagement with queer and trans theoretical literature that raises questions about restrictive social systems governing thought regarding gendered and sexual regulatory norms. The focus is on examining pedagogical matters related to both interrupting heteronormativity and addressing what comes to be recognized as a viable gendered personhood through employing Lesbian, Gay, Bisexual, Transgender, Queer (LGBTQ)-themed texts in schools. The paper concentrates on investigating the insights of one queer-identifying elementary school teacher as she reflects on the pedagogical potential of deploying literacy resources for discussing themes such as same-sex families and relationships, and transgendered and gender diverse subjectivities in the classroom. The study builds on research by Caitlin Ryan, Jasmine Patraw, Maree Bednar, Mollie Blackburn, and J.F. Buckley to highlight both the possibilities and limits faced by this teacher in dealing with sexual minority issues and diverse gender identities and expressions as part of the everyday school curriculum. Implications of the research for pre-service teacher education and for the professional learning of teachers more generally are outlined.